2011
DOI: 10.1007/s11270-010-0737-x
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Immobilized Pseudomonas fluorescens SM1 Strain for Remediation of Phenols, Heavy Metals, and Pesticides from Water

Abstract: Immobilized microbial cells for the biological treatment have the potential to degrade toxic chemicals faster than conventional wastewater treatment systems. In the present study, suitability of immobilized Pseudomonas fluorescens SM1 strain in calcium alginate beads for remediation of the major toxicants in Indian water bodies was tested by means of GC/HPLC and AAS techniques. Roughly 80% reduction in the concentration of phenols was observed by immobilized SM1 cells compared with 60% by the free cells. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Among PGPR species, fluorescent pseudomonads are frequently recovered from both the soil and plant rhizospheres. Among these, Pseudomonas fluorescens is a well-known soil and rhizosphere inhabitant (Van Elsas et al 2006) that can tolerate high concentrations of heavy metals in polluted waters (Wasi et al 2010). Its utilisation as a seed bioinoculant for hyperaccumulator plants is currently unknown, and there are very few studies aimed at investigating its capability for increasing the metal availability of the rhizospheres of such plants (Dell'Amico et al 2008;Sheng et al 2008).…”
mentioning
confidence: 99%
“…Among PGPR species, fluorescent pseudomonads are frequently recovered from both the soil and plant rhizospheres. Among these, Pseudomonas fluorescens is a well-known soil and rhizosphere inhabitant (Van Elsas et al 2006) that can tolerate high concentrations of heavy metals in polluted waters (Wasi et al 2010). Its utilisation as a seed bioinoculant for hyperaccumulator plants is currently unknown, and there are very few studies aimed at investigating its capability for increasing the metal availability of the rhizospheres of such plants (Dell'Amico et al 2008;Sheng et al 2008).…”
mentioning
confidence: 99%
“…Researchers have indicated that immobilized cells of P. fluorescens SM1 strain were quite effective in bioremediation of major toxicants present in Indian water bodies, including heavy metal [26]. The functional groups such as hydroxyl, carboxyl, amide, and phosphate groups which identified on P. fluorescens surface by FTIR technique could possibly be involved in the metal binding of Zn, Co, Cd, Pb, Cu, Cr, and Fe [27].…”
Section: Characterization Of Potential Bacteriummentioning
confidence: 99%
“…Several studies conducted in India demonstrated the presence of various pollutants in surface waters with the major toxicants being heavy metals, pesticides and phenolics (CPCB 1995;Handa 1992;Ahmad 2009, 2011a;Wasi et al 2010Wasi et al , 2011. Various decontamination strategies have thus gained momentum in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Various decontamination strategies have thus gained momentum in recent years. Bioremediation has been used as a preferred strategy to remove pollutants, not necessarily completely but to convert into the substances with decreased solubility and toxicity (Kamaludeen et al 2003;Wasi et al 2010Wasi et al , 2011. Pseudomonas strains have been found to degrade a large number of substances (Bhat et al 1994;Roane et al 2001).…”
Section: Introductionmentioning
confidence: 99%